Appraisal of Noise Level Dissemination Surrounding Mining and Industrial Areas of Keonjhar, Odisha: a Comprehensive Approach Using Noise Mapping - LOKHANDE, Satish Krishna; DHAWALE, Satyajeet A.; PATHAK, Samir S.; GAUTAM, Rakesh; JAIN, Mohindra C.; BODHE, Ghanshyam L. (Archives of Acoustics, 2017)
Noise mapping is a well-established practice among the European nations, and it has been follow for almost two decades. Recently, as per guidelines of the Directorate General of Mines Safety (DGMS), India, noise mapping has been made mandatory in the mining expanses. This study is an effort to map the noise levels in nearby areas of mines in the northern Keonjhar district. The motive of this study is to quantify the existing A-weighted time-average sound level (LAeq, T ) in the study area to probe its effects on the human dwellings and noise sensitive areas with the probability of future development of the mines, roads, and industrial and commercial zone. The LAeq, T was measured at 39 identified locations, including industrial, commercial, residential, and sensitive zones, 15 open cast mines, 3 major highways, and 3 haulage roads. With the utilisation of Predictor LimA Software and other GIS tools, the worked out data is mapped and noise contours are developed for the visualisation and identification of the extent and distribution of sound levels across the study area. This investigation discloses that the present noise level at 60% of the locations in silence and residential zone exposed to significantly high noise levels surpasses the prescribed limit of Central Pollution Control Board (CPCB), India. The observed day and night time $L_{Aeq, T}$ level of both zones ranged between 43.2–62.2 dB(A) and 30.5–53.4 dB(A), respectively, whereas, the average $L_{dn}$ values vary between 32.7 and 51.2 dB(A). The extensive mobility of heavy vehicles adjoining the sensitive areas and a nearby plethora of open cast mines is the leading cause of exceeded noise levels. The study divulges that the delicate establishments like schools and hospitals are susceptible to high noise levels throughout the day and night. A correlation between observed and software predicted values gives $R^2$ of 0.605 for $L_d$, 0.217 for $L_n$, and 0.524 for $L_dn$. Finally, the mitigation measure is proposed and demonstrated using a contour map showing a significant reduction in the noise levels by 0–5.3 dB(A).